CD 4 count stratification and its accuracy in predicting the HIV-Tuberculosis co-infection - Sadiq, Hina; Akhtar, Nasim; Virk, Sana; Virk, Kazim Abbas; Zafar, Abeer; Meraj, Lubna (Infectious Diseases Journal of Pakistan, 2024)
Background: Co-infection of HIV and TB is a significant public health concern. The relationship between increased HIV replication and low CD4+-TLC in HIV-positive patients with treatment interruptions is well documented. Moreover, TB preventive therapy is highly effective in reducing TB incidence and mortality among HIV-positive patients. The objective of this study was to stratify in terms of different ranges and see the association of CD4+ T-lymphocyte count with different presentations of TB in HIV-positive patients. Material and Methods: This observational cross-sectional study was conducted from October 2022 to March 2023. A total of seventy-four outdoor and indoor patients were enrolled. Patient data were collected using a structured questionnaire. The MTB gene Xpert, screening for HIV, and CD4+ T-lymphocyte count testing was performed. All the patients aged> 18 years who were found to have positive HIV rapid tests and microbiologically confirmed tuberculosis were included in the study. The CD 4 count was stratified in terms of ranges. The data was analyzed using SPSS 29. The association was established by Spearman’s coefficient and odd ratios keeping the significance level <0.05. Results: 74 patients were enrolled in the study, out of which 67 (90.5%) were males and 7 (9.5%) were females. The mean age of study participants was 38.33 ± 11.43 years (21-78 years) and the mean CD4 count was 85.7 ± 59.48. Most frequent was pulmonary TB; 43 (44.5%) followed by disseminated TB; 11 (24.3%), pleural TB; 9 (9.4%), and TB meningitis 6 (8.1%). There was no association between CD4+ T-lymphocyte count and the site of involvement of TB (p>0.05). Pulmonary TB, miliary TB, TB brain abscess, tuberculomas, and disseminated TB were found more at CD 4 count <100 as signified by the Odd Ratios (1.1, 1.3, 1.3, 1.3, 1.01 within 95% CI)). On the other hand, Pleural TB, Spinal TB, TB lymph adenitis, and TB meningitis were found at CD4 count >100 (4.5, 2.3, 1.51 respectively within 95%CI. Conclusion: Among HIV-TB co-infected individuals, the frequency of pulmonary TB was found to be highest followed by disseminated TB and pleural TB. No association was found between CD4+ Lymphocyte count and different presentations of TB in this study. The CD4 count is a poor predictor of HIV/TB co-infection unless it is <100. Mostly tuberculosis occurred at count <100 as depicted by odd ratios. Keywords: CD4+ T-lymphocyte count, Extrapulmonary tuberculosis, HIV-TB co-infection, Pulmonary tuberculosis